The Effect of Liquidity, Leverage and Company Size on Company Value with Profitability as an Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2021 - Muhammad Mumtazal Fikri*; Atwal Arifin (Riwayat: Educational Journal of History and Humanities, 2023)
The aim of this research is to determine the influence of liquidity, leverage and company size on company value with profitability as a moderating variable in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2019-2021. Samples were taken based on predetermined criteria using the purposive sampling method. Data that meets the criteria amounts to 83 companies. The sample processing method uses moderated regression analysis (MRA) using the SPSS application. The results obtained in this research are that liquidity has no effect on company value, leverage has an effect on company value, company size has no effect on company value, and profitability is only able to moderate the relationship between company size and company value. These results indicate that companies need to improve liquidity performance and pay attention to profitability performance in order to increase company value which will provide a positive signal to investor.